Time-Frequency Analysis of Horizontal Vibration for Vehicle-Track System Based on Hilbert-Huang Transform. (8th December 2013) - Li, Zaiwei; Lian, Songliang; He, Yuelei
Abstract : Relationship between track alignment irregularity and car body horizontal vibration acceleration is analyzed by using Hilbert-Huang Transform (HHT). Actual measured alignment irregularity and car body horizontal vibration acceleration are decomposed by empirical mode decomposition (EMD) to obtain intrinsic mode function (IMF). By comparing IMF waveform and energy spectrum of the irregularity and vibration acceleration, there is the definitive correspondence of IMFs, and the adverse section of irregularity can be identified from car body horizontal vibration acceleration. Finally, regression analysis is taken for measured sample of track inspection car on Beijing-Guangzhou line; the quantitative relationship between track alignment irregularity and car body horizontal vibration acceleration is established with a wavelength between 1.5 m and 50 m.